2019
DOI: 10.1111/jace.16645
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of the indentation fracture of fused silica

Abstract: It is unclear how the densification of fused silica influences the damage of its precision optics subjected to machining. This paper presents a quantitative analysis of the indentation fracture of fused silica involving densification with the embedded center of dilation (ECD) model. The Hertzian stress field and the ECD‐induced stress field were superposed to provide the overall stress distribution in the loading stage. A new method was established to accurately determine the strength of the ECD‐induced stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…When considering different flaw populations (eg, surface, bulk, shear‐fault), it becomes increasingly complicated to experimentally validate analytic results beyond affirming the presence and orientation of a tensile maximum principal stress. In practice, sharp indentation analytic models are verified with FEA 26,68,69 …”
Section: Resultsmentioning
confidence: 98%
“…When considering different flaw populations (eg, surface, bulk, shear‐fault), it becomes increasingly complicated to experimentally validate analytic results beyond affirming the presence and orientation of a tensile maximum principal stress. In practice, sharp indentation analytic models are verified with FEA 26,68,69 …”
Section: Resultsmentioning
confidence: 98%
“…It is well known that in indentation, brittle materials exhibit a characteristic crack system including median cracks, radial cracks, lateral cracks, and cone cracks [6,7]. The crack system in glass was confirmed by crosssectional observation along the median/radial cracks [8][9][10]. Real-time observation of crack evolution during loading/unloading was also accomplished [6,11].…”
Section: Introductionmentioning
confidence: 88%
“…In the finite element model, an infinitely sharp Berkovich edge-forward indenter slides along the x -axis on the top surface of a deformable parallelepiped with a dimension of W × W × ( l + 2 W ), as shown in Figure 2 . The diamond indenter is assumed to be rigid because its Young’s modulus [ 32 ] and hardness [ 33 ] are much higher than those of the fused silica samples [ 14 ]. An eight-node linear brick element with reduced integration and hourglass control is used.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…It is reported that the stress and deformation are relieved by densification [ 13 , 25 ]. The stress distribution is significantly influenced by the geometry and location of the elastic–plastic boundary [ 14 , 37 ]. In the analytical models of sliding stress fields, e.g., the Ahn model [ 16 ] and the Wang model [ 17 ], the plastic region is assumed to be a sphere with the center on the sample surface.…”
Section: Deformation and Fracture In Fused Silica Under Scratchingmentioning
confidence: 99%
See 1 more Smart Citation